Orthodontics at Times of National Emergency: Past and Current Crises Part 2. COVID-19: Implications for Clinical Practice. (2nd July 2020) - Lee, Tara V N; Fowler, Peter V; Williams, Julie C; Ellis, Pamela; Atack, Nikki E; Ireland, Anthony J
Abstract : This paper explores the disease COVID-19 caused by the SARS-CoV-2 virus. This disease has caused a global pandemic affecting the way society both works and lives. COVID-19 is spread through droplets from the mouth and nose, which has implications for how we practice orthodontics. Our clinical practice will therefore need to be adapted to keep both patients and staff safe. This paper addresses the adaptations that should be considered. We also address what the future of orthodontics may look like in light of the issues with cross infection that COVID-19 has raised. CPD/Clinical Relevance : How to adapt our clinical practice to keep both staff and patients safe.